Working memory deficits in neuronal nitric oxide synthase knockout mice: Potential impairments in prefrontal cortex mediated cognitive function - Zoubovsky, Sandra P.; Pogorelov, Vladimir M.; Taniguchi, Yu; Kim, Sun-Hong; Yoon, Peter; Nwulia, Evaristus; Sawa, Akira; Pletnikov, Mikhail V.; Kamiya, Atsushi (Biochemical and biophysical research communications, 2011)
► nNOS knockout mice exhibit mild impairments in object recognition memory. ► nNOS knockout mice display working memory deficits, potential impairments in prefrontal cortical functioning. ► nNOS interacts with DISC1, another genetic risk factor for schizophrenia that plays roles for cortical development and prefrontal cortex functioning, in the developing cerebral cortex. ► DISC1–NDEL1 interaction is increased in nNOS knockout mice. ► nNOS knockout mice are useful tools in studying the role of nNOS signaling in cortical development and prefrontal cortical functioning. Neuronal nitric oxide synthase (nNOS) forms nitric oxide (NO), which functions as a signaling molecule via S-nitrosylation of various proteins and regulation of soluble guanylate cyclase (cGC)/cyclic guanosine monophosphate (cGMP) pathway in the central nervous system. nNOS signaling regulates diverse cellular processes during brain development and molecular mechanisms required for higher brain function. Human genetics have identified nNOS and several downstream effectors of nNOS as risk genes for schizophrenia. Besides the disease itself, nNOS has also been associated with prefrontal cortical functioning, including cognition, of which disturbances are a core feature of schizophrenia. Although mice with genetic deletion of nNOS display various behavioral deficits, no studies have investigated prefrontal cortex-associated behaviors. Here, we report that nNOS knockout (KO) mice exhibit hyperactivity and impairments in contextual fear conditioning, results consistent with previous reports. nNOS KO mice also display mild impairments in object recognition memory. Most importantly, we report for the first time working memory deficits, potential impairments in prefrontal cortex mediated cognitive function in nNOS KO mice. Furthermore, we demonstrate Disrupted-in-Schizophrenia 1 (DISC1), another genetic risk factor for schizophrenia that plays roles for cortical development and prefrontal cortex functioning, including working memory, is a novel protein binding partner of nNOS in the developing cerebral cortex. Of note, genetic deletion of nNOS appears to increase the binding of DISC1 to NDEL1, regulating neurite outgrowth as previously reported. These results suggest that nNOS KO mice are useful tools in studying the role of nNOS signaling in cortical development and prefrontal cortical functioning.